Scientometric approach to the scientific trends in articles on seagrass in the Atlantic Coast published between 1969-2024 - Souza, Luiza Reis de; Pereira, Renato Crespo; Soares-Gomes, Abílio (Frontiers in Plant Science, 2024)
Submerged or partially floating seagrasses in marine or brackish waters form productive seagrass beds, feeding grounds for a rich and varied associated biota, play key ecological roles in mitigating climate change and provide ecosystem services for humanity. The objective of this study was to perform a temporal quali- and quantitative analysis on the scientific production on seagrasses in the Atlantic Ocean during last 64 years (1960 to 2024) through defined workflow by scientometric analysis on Scopus database. Publications in this database date back to 1969, comprising a total of 3.482 scientific articles, primary focused on seagrass ecology. These articles were published in 574 distinct peer-reviewed scientific ecological journals, and are divided into four periods based on the number of articles, keywords and biograms, with an average annual increase of 8.28% in the number of articles published. Zostera marina, Halodule wrightii and Thalassia testudinum were the most researched species, especially in Atlantic coastal areas of Europe and North/Central America. Studies on seagrasses along the Atlantic coast have been well consolidated by a few authors with prolific scientific output, but much of the research has been conducted by non-specialists who published only one or a few articles. We also found that researches from each continent tend to focus on specific topics: North America researches investigated future climate change scenarios and seagrass ecology, while those from Europe prioritize on restoration plans. Additionaly, European researchers from Europe predominantly collaborate with local scientists, a trend also observed among American researches. This indicates a need for increase research and scientific production in the South Atlantic region.